The influence of the geroprotective cytokine on the transcriptome of young and senescent mesenchymal stem cells - Liya G. Kondratyeva; Diana K. Matveeva; Maria I. Ezdakova; Marina V. Utkina; Andrey Yu. Ratushnyy (BMC Research Notes)
Abstract Objectives Increasing longevity and the growing elderly population necessitate a deeper understanding of aging mechanisms to prolong productive life and improve treatments for age-related diseases linked with cellular senescence. Mesenchymal stem cells (MSCs) are crucial for maintaining tissue homeostasis, but their physiological changes during senescence are not well understood. Growth differentiation factor 11 (GDF11) has emerged as a potential rejuvenation factor, enhancing MSC viability, mobility, and angiogenic functions, which improves outcomes in ischemic models and cardiac repair. This study aims to identify transcriptomic changes in young and senescent MSCs influenced by GDF11, highlighting its potential in MSC-based therapies. Data description To evaluate transcriptomic changes induced by the potential geroprotective factor GDF11, we performed RNA sequencing on four groups of samples: ‘young’ MSCs (MmC-/GDF11-) and senescent MSCs (MmC+/GDF11-) without the addition of GDF11, as well as ‘young’ (MmC-/GDF11+) and senescent MSCs (MmC+/GDF11+) with the addition of GDF11. After 10 days of incubation, indexed cDNA libraries for Illumina sequencing were prepared from the samples, and the resulting cDNA library mix was subjected to NovaSeq 6000 sequencing. This paper describes the collection of 16 RNA sequencing samples comprising 4 sets of MSCs. FASTQ files from Illumina sequencing are available in the NCBI Gene Expression Omnibus.